The summer Hikaru died. 2 - Mokumokuren (Yen Press, 2023)
Yoshiki tried to pretend nothing was wrong, but the truth cannot be ignored. Hikaru is gone. This new "Hikaru" might be dangerous. But "Hikaru" seems to want nothing more than to befriend and protect Yoshiki. Despite Rie's warnings, Yoshiki decides to extend the hand of friendship, hoping it will help "Hikaru" become more human. But in doing so, what might Yoshiki become?